Emotion, Memory, Meaning, Directions A Response to Kirsten Marie Hartvigsen and Thomas J. Kraus - Emde Boas, Evert van 1982- (2021)
This response article reviews the contributions of Kirsten Marie Hartvigsen and Thomas Kraus to this special issue, and uses them as the basis for a discussion of some theoretical and methodological issues relevant to cognitive narratology and cognitive literary studies more broadly. Without offering substantial answers itself, the response poses questions concerning (i) the compatibility of different scientific frameworks used in cognitive models of characterization, particularly in the light of currently dominant ‘4ea’ models of cognition (there is a particular focus on the relationship between affective and (other) cognitive aspects of reader response, and on the role of memory); and (ii) the adaptability of cognitive models to dealing with “synthetic” and “thematic” (as opposed to “mimetic”) aspects of literary character. A brief conclusion argues for two-way traffic between the cognitive sciences and literary criticism.
Keywords: character ontology; Memory; affective literary response; 4ea cognition; cognitive literary studies; cognitive narratology